Peran Kualitas Bahan Baku dan Kualitas Produk dalam Proses Produksi di PT Adi Satria Abadi - Afila, Rofina; Utami, Kristiana Sri (Populer: Jurnal Penelitian Mahasiswa, 2024)
Increasing the results of high quality products is one of the main objectives of production process activities carried out in a manufacturing company. This research aims to determine the production process at PT Adi Satria Abadi. This research uses library research, also known as a literature review, while the data analysis technique uses qualitative descriptive techniques. This technique aims to analyze a problem that occurs in a study, namely PT. Adi Satria Abadi. The results of this research explain that the quality of raw materials and product quality is very important in the production process.